Non-thermal Processing Technologies for Dairy Products: Their Effect on Safety and Quality Characteristics - Neoκleous, Ioanna; Tarapata, Justyna; Papademas, Photis (My University, 2022)
Thermal treatment has always been the processing method of choice for food treatment in order to make it safe for consumption and to extend its shelf life. Over the past years non-thermal processing technologies are gaining momentum and they have been utilized especially as technological advancements have made upscaling and continuous treatment possible. Additionally, non-thermal treatments are usually environmentally friendly and energy-efficient, hence sustainable. On the other hand, challenges exist; initial cost of some non-thermal processes is high, the microbial inactivation needs to be continuously assessed and verified, application to both to solid and liquid foods is not always available, some organoleptic characteristics might be affected. The combination of thermal and non-thermal processing methods that will produce safe foods with minimal effect on nutrients and quality characteristics, while improving the environmental/energy fingerprint might be more plausible.
Keywords: functionality; microbiology; mild-processing; non-thermal dairy; quality; safety; UV-C